ショウワ キチ アイスランド チジキ キョウヤクテン カンソク - 佐藤, 夏雄; サトウ, ナツオ; 勝田, 豊; カツタ, ユタカ; 鮎川, 勝; アユカワ, マサル; 福西, 浩; ヒクニシ, ヒロシ; 平沢, 威男; ヒラサワ, タケオ; SATO, Natsuo; KATSUTA, Yutaka; et al. (国立極地研究所, 1979)
P(論文) 1977年7月29日から9月18日まて,南極昭和基地のほほ地磁気共役点にあたるアイスランドのHusafellにおいて,フラソスとの共同観測を行った地磁気脈動,ELF・VLFエミッション,オーロラ観測等を行ったか,この論文ではELF・VLFエミッションの解析結果を報告する.それによれは,1)早朝出現するオ-ロラコーラスの共役性は悪く,北半球側て強い.2)昼間現れるコーラスの共役性は良いか,受信周波数は絹半球ては低周波数帯域か強く北半球ては高周波数帯域か強い.3)QPエミッションは両半球同時に受信される.4)オーロラヒスの共役性は悪く,南半球(冬半球)側か圧倒的に強い等のことか明らかになった. Conjugate observations of ELF-VLF emissions, geomagnetic pulsations and auroras were carried out at Syowa Station in Antarctica and at Husafell in Iceland from July 29, 1977 to September 18, 1977 Husafell is located at a distance of about 60 km from the conjugate point of Syowa From a prelimmary analysis of the ELF and VLF emission data, the following results were obtained 1) Conjugacy of auroral chorus emissions observed in the early morning is low. The emission intensity is larger at Husafell than at Syowa. 2) Daytime ELF chorus emissions show a good conjugacy. However, it is found that the intensity in the low frequency range is greater at Syowa than at Husafell, and vice versa in the high frequency range. 3) QP emissions are observed simultaneously at the conjugate-pair stations. 4) Conjugacy of auroral hiss emissions is generally low during this observation period. The intensity is much higher at Syowa (winter hemisphere) than at Husafell (summer hemisphere) departmental bulletin paper